Modelagem e estimação de parâmetros genéticos e fenotípicos para pesos do nascimento à seleção (378 dias) de machos Nelore - Cyrillo, JNDG; de Alencar, M. M.; Razook, A. G.; Mercadante, MEZ; de Figueiredo, L. A. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2004)
Genetic parameters for weights (17, 942 records), obtained in intervals of 60 days, from the birth to selection (378 days of age), of 2,582 males of the Nellore breed was estimated in univariate analyses by the Maximum Restricted Likelihood method. The models of analysis models included the fixed effects of contemporary groups, month of birth, mother age and age when the weights were collected as covariate. Three models differing in random effects were tested: the model 1 (M1) was adjusted for the direct and maternal addictive genetic effects and maternal permanent environment; in model 2 (M2) the maternal genetic effect was excluded; and the model 3 (M3) was only adjusted for the direct addictive genetic effect. The test of likelihood (LRT) detected significant differences, for all the ages, of M2 and M1 in relation to the simple model (M3), evidencing the importance of the maternal effects. Except for the birth weight (0.40), low values (0.05 to 0.12) of h(2) were found for M1 and M2 until 8 months of age and, after this period, reasonable increase could be observed, reaching 0.28 until 13 months of age. The estimates of the total variance fraction, due to the effect of maternal permanent environment, were high and practically became unaffected between the models 1 and 2. Maternal effects, not necessarily decomposed (in genetic addictive and permanent environment), affected the Nellore males growth. Models that contemplate maternal effects, besides the genetic addictive direct effects, are more realistic to describe the trajectory of the variances in the initial phases of growth of Nelore male calves.
Modeling and estimation of genetic parameters for weights from birth to selection age (378 days) of nellore males
Keywords: beef cattle; heritability; maternal effects; repeated records; subsequent ages; variance components